Proposing Green Waqf Development Strategy in Protecting Land Ecosystems in Indonesia: An Interpretive Structural Modeling Approach - Mohammad Iqbal Irfany; Sri Rahayu Ningsih; Qoriatul Hasanah; Aam Slamet Rusydiana (SMART Insight, 2023)
Climate change and terrestrial ecosystems are one of the important things in sustainable development goals (SDGs). In Indonesia, there are about 14 million critical lands (The Ministry of Environment and Forestry, 2018) that motivated the formation of several innovative financing to utilize critical lands, including the Green Waqf Movement since August 2021. This study aims to describe, identify key sub-elements, and analyze the Green Waqf development strategy in maintaining terrestrial ecosystems in Indonesia through the Interpretive Structural Modeling (ISM) approach. The results show that several key aspects in the constraint element are the lack of professionalism of nazhir, the lack of low public literacy and the lack of education and socialization of Green Waqf in the development of Green Waqf. The main goal that needs to be achieved is the existence of legal support for Green Waqf. This study recommends Green Waqf development strategies by coordinating the Indonesian Waqf Board, WaCIDS, nazhir, The Ministry of Environment and Forestry, local governments and other related stakeholders to encourage the Green Waqf program. In addition, approaching and fostering good relationship between wakif, nazhir, and business (including SMEs) as well as developing a number of green product development programs are also important.